2023
DOI: 10.7759/cureus.34514
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Subacute Combined Degeneration Due to Nitrous Oxide-Induced Vitamin B12 Deficiency

Abstract: Nitrous oxide, also known as “laughing gas,” is a naturally occurring gas that is colorless, odorless, nonflammable, and nontoxic. It has been used as an inhalant anesthetic in the medical field for more than 150 years for dental and surgical procedures. Due to its wide availability and ability to cause euphoria, its recreational use is on the rise. We present a case of subacute combined degeneration (SCD) due to nitrous oxide-induced vitamin B12 deficiency. The patient presented with bilateral lower extremity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…However, Farina et al recommended a much higher dose rate (15 mg rivaroxaban twice a day in the first four weeks and 10 mg oral rivaroxaban with 100 mg aspirin per day for six months) compared to our study [ 17 ]. Several other case studies have also reported the use of rivaroxaban to prevent the recurrence of MTS [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Farina et al recommended a much higher dose rate (15 mg rivaroxaban twice a day in the first four weeks and 10 mg oral rivaroxaban with 100 mg aspirin per day for six months) compared to our study [ 17 ]. Several other case studies have also reported the use of rivaroxaban to prevent the recurrence of MTS [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Một nghiên cứu khác tại Bệnh viện Đại học Y Từ Châu, các mức đốt sống bị suy giảm phổ biến nhất là C3, C4 và C5 (50,6% mỗi loại), tiếp theo là C2 (41,6%) và C6 (37,2%) [4]. Có nhiều báo cáo, nghiên cứu về các trường hợp ngộ độc N2O, bệnh nhân có các dấu hiệu điển hình của thoái hóa tủy sống bán cấp trên cộng hưởng từ cùng với giảm nồng độ vitamin B12 [9], tuy nhiên chưa có nghiên cứu nào đánh giá trực tiếp nồng độ vitamin B12 có liên quan đến tổn thương trên cộng hưởng từ tủy sống.…”
Section: đặC đIểm Xét Nghiệm Cận Lâm Sàngunclassified